2014
DOI: 10.1007/s00464-014-3769-2
|View full text |Cite
|
Sign up to set email alerts
|

Consumer demand for surgical innovation: a systematic review of public perception of NOTES

Abstract: This review suggests significant public interest in NOTES and scarless surgery in general. Further research and consideration of differences in public perceptions across regions, countries and cultures are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The fact that there are over 7000 da Vinci (and few hundred other RAMIS) systems now in daily clinical use shows that this form of surgical robotics is popular among the public, helping in general the rise of new systems via new investments [103].…”
Section: Discussion a N D F U T U R E P R O S P E C T Smentioning
confidence: 99%
“…The fact that there are over 7000 da Vinci (and few hundred other RAMIS) systems now in daily clinical use shows that this form of surgical robotics is popular among the public, helping in general the rise of new systems via new investments [103].…”
Section: Discussion a N D F U T U R E P R O S P E C T Smentioning
confidence: 99%
“…It bears mentioning that the decision to refuse transvaginal NOTES for cholecystectomy is mainly based on moral grounds. Whether the surveyed health professionals represent a potentially biased sample 11 and/or the interpretations of the results of public surveys have to be done cautiously because the public does not have the appropriate background 14 remains a point of disagreement in recently published literature. However, in our study, multinominal logistic regression analyses identified availability of medical education as a relevant factor for the preference of surgical intervention for both ovariectomy and even more pronounced for cholecystectomy when derived from comparison among religious groups.…”
Section: Discussionmentioning
confidence: 99%
“…12-14 The transvaginal route was preferred to the transrectal route because of less chance of bacterial or fecal contamination of the peritoneal cavity. 15 In this experiment, the transrectal route was chosen as it can more or less simulate the transvaginal cholecystectomy in humans. It is anticipated that accessing through the pig’s vagina would be very difficult due to its size.…”
Section: Discussionmentioning
confidence: 99%